Protocol for isolating leukemia-derived extracellular vesicles from the spleen of preclinical models of leukemia using ultracentrifugation - Gargiulo, Ernesto (2024)
Here, we present a protocol for the direct isolation of small extracellular vesicles (sEV) from the spleen of preclinical murine models of leukemia using ultracentrifugation. We describe steps for tissue collection, sample preparation, ultracentrifugation-based isolation, and sEV characterization. This protocol allows for efficient enrichment of both leukemia and its microenvironment-derived sEV (LME-sEV), providing a valuable tool for studying their composition and functional roles. Potential applications include investigating the role of sEV in leukemia progression and identifying biomarkers.